Multiagency Response to Childhood Sexual Abuse: A Case Study that Explores the Role of a Specialist Centre. (10th August 2017) - Voss, Lindsay; Rushforth, Helen; Powell, Catherine
Abstract : Through the application of case study methods, this research explored the role of a specialist centre that responds to actual or suspected childhood sexual abuse (CSA). When CSA is suspected to have occurred, children and families and professionals from statutory agencies are required to navigate complex processes. This study was undertaken to explore those processes in a specialist children's referral centre. It comprised three datasets: (1) 60 children (0–17 years) were 'tracked' to ascertain reasons for referral, the type of examination and outcomes in terms of health, social care and criminal justice actions; (2) semi‐structured interviews with 16 professionals (paediatricians, specialist nurses, child abuse investigation police officers and children's social workers); and (3) analysis of 'patient' and parent/carer satisfaction questionnaires. Medical examination rarely confirmed abuse and only 13 per cent of cases were pursued within the criminal justice system. However, 66 per cent of children had an identified health need requiring follow‐up. Professionals from all groups believed the centre provided a 'child friendly' facility that enhanced co‐operation. However, challenges with focusing on the needs of children and with mulitagency working were identified. Routine patient satisfaction data collected at the time of the study demonstrated positive views of the care received, although other data suggest that this may be an incomplete picture. 'This research explored the role of a specialist centre that responds to actual or suspected childhood sexual abuse' Key Practitioner Messages: Medico‐legal considerations may dominate health assessment of children when CSA is suspected and yet only a small proportion of cases proceed to court. A specialist centre can provide a child‐friendly environment and enhance interprofessional communication. A high proportion of children referred to statutory services following suspected CSA have a range of health and psychosocial needs that require further follow‐up. Roles that cross professional boundaries may enhance CSA services but this concept requires further research. 'A specialist centre can provide a child‐friendly environment and enhance interprofessional communication'